Searching for New Tools to Counteract the Helicobacter pylori Resistance: The Positive Action of Resveratrol Derivatives - Paola Di Fermo; Silvia Di Lodovico; Rosa Amoroso; Barbara De Filippis; Simonetta D'Ercole; Emanuela Di Campli; Luigina Cellini; Mara Di Giulio (MDPI AG, 2020)
The drug-resistance phenomenon in Helicobacter pylori underlines the need of novel strategies to improve the eradication rate including alternative treatments combining antibiotic and non-antibiotic compounds with synergistic action. In this study, the antibacterial (MIC/MBC) and anti-virulence effects (biofilm reduction and swarming motility inhibition) of resveratrol-RSV and new synthetized RSV-phenol derivatives, with a higher bioavailability, alone and combined with levofloxacin-LVX were evaluated against resistant H. pylori clinical strains. The experiments were confirmed in vivo using the Galleria mellonella model. Among the studied RSV derivatives, RSV-3 and RSV-4 possessed higher antibacterial activity with respect to RSV (MICs from 6.25 to 200 µg/mL and from 3.12 to 200 µg/mL, respectively). RSV, RSV-3, and RSV-4 were able to synergize with LVX restoring its effect in two out of seven clinical resistant strains tested for the study. RSV, RSV-3, and RSV-4, alone and with LVX at sub-MIC and sub-synergistic concentrations, significantly reduced the biofilm formation. Moreover, RSV-3 and RSV-4 reduced the H. pylori swarming motility on soft agar. RSV, RSV-3, and RSV-4 were non-toxic for G. mellonella larvae and displayed a protective effect against H. pylori infection. Overall, RSV-phenol derivatives should be considered interesting candidates for innovative therapeutic schemes to tackle the H. pylori antibiotic resistance.